ElboSense: A Novel Capacitive Strain Sensor for Textile-Based Elbow Movement Monitoring - Al Rumon M.A.; Ravichandran V.; Veeturi S.; Owens J.; Kumar D.; Solanki D.; Mankodiya K. (My University, 2025)
The field of wearable sensors has witnessed remarkable progress in recent years, enabling real-time monitoring of musculoskeletal biomechanics. Musculoskeletal injuries require long-term management through medications and physical therapy to ensure a smooth recovery. Assessment of a patient's range of motion (ROM) is an essential component of physical therapy. However, existing methods for measuring ROM are either analog or require expensive equipment. In this work, we present ElboSense, a smart textile-based sensing solution to monitor elbow motion precisely. ElboSense is embedded with a novel yarn-like capacitive strain sensor made with braided composite structures of multiple filament strands in a helical pattern. We seamlessly integrated the sensor into an elbow brace and developed an embedded system for data acquisition. The work conducted a study with eight healthy adult participants who performed a regulated elbow movement exercise (flexion and extension) 10 times. We validated the sensor measurements against a reliable optical motion-capture system. The average cross-correlation was found to be 0.91. Pearson's correlation coefficient analysis showed 0.95 for peak-to-peak and 0.98 for valley-to-valley. All the preliminary results indicate a good agreement and reliability as a potential sensing solution to monitor the range of motion during elbow exercises. © 2023 IEEE.